Sex and Relationship Education for the Autonomy and Emotional Well-Being of Young People - Marí-Ytarte, Rosa; Moreno-López, Roberto; Barranco-Barroso, Rut (Frontiers in Psychology, 2020)
In the transition to adulthood, sexuality and emotional relationships constitute one of the most important dimensions for the achievement of personal autonomy and emotional well-being. Despite advances in sex education, sexuality and relationships remain conflictive areas in the development of young people. Inequalities between men and women, gender identities and sexual violence, along with the beliefs and expectations surrounding these issues, persist as handicaps to having a fulfilling relationship and sex life. At this stage, emotional well-being is also consolidated by one’s perception of sexuality and relationships from models learned in childhood, in which gender stereotypes and sexuality based on relationships of domination and discrimination persist. Therefore, we examined how the sexual beliefs and practices reported by young people correlate with their level of personal autonomy and responsibility in terms of risky behaviors and toxic relationships. The study shows the extent to which sexual beliefs and habits are linked to decision-making, personal development and social problems derived from conflictive relationships, affecting young people’s overall well-being. A questionnaire was developed based on the theoretical constructs of comprehensive sexuality and equality education (UNESCO, 2010, 2018; WHO, 2010) with the following dimensions: sex education, sexual habits and practices, motivations, concepts and beliefs about sexuality. It was distributed in institutions of higher education (N452) in Spain, Portugal, Argentina and Brazil, and the results revealed a discrepancy between the reported practices and behaviors and the beliefs and models of reference. Key issues included sexuality and relationships as an aspect of personal life that generates confusion and conflict, as well as the propagation of gender and sexist stereotypes that influence young people’s emotional well-being.